The Thermal Energy Influence on the Surface Layer of Construction Steels during Laser Beam Cutting - Ovsik, Martin; Stanek, Michal; Hylova, Lenka; Manas, Miroslav; Stoklasek, Pavel (Manufacturing Technology Journal, 2019)
The presented article deals with the thermal energy influence on various types of construction steels during laser beam cutting. When the material is cut by a laser, the workpiece is subjected to intensive thermal load. Due to this influence, steels hardness is increased and the structure is changed.The aim of this study is to verify how the thermal energy influences the surface layer of material during laser cutting. The influence was studied on data measured by DSI (depth sensing indentation) micro-hardness method. Each sample was subjected to cross-section from edge to the distance of 20 mm from the edge measurement. To evaluate surface layers during laser cutting, three types of steels with different carbon content 1.0038 (S235JR), 1.1203 (C55) a 1.7131 (16MnCr5) were chosen. The main objective was to determine the distance from the cutting point to the material when cutting with a laser beam, how its micro-mechanical properties and structure change or the distance from the cutting point to the component's hardening.
Keywords: Laser beam; thermal influence; steels; indentation hardness; indentation modulus